2015
DOI: 10.3109/03014460.2015.1013986
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to ambient air pollution-does it affect semen quality and the level of reproductive hormones?

Abstract: The present study provides suggestive evidence of an association between ambient air pollution and sperm quality. Further research is needed to explore this association in more detail. Individual precise exposure assessment would be needed for more detailed risk characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 30 publications
4
82
2
1
Order By: Relevance
“…Previous studies suggested that exposure to NO 2 (or NO x ) and CO were associated with increased abnormalities in sperm morphology, 12,19 but not associated with sperm concentration, count, motility, nor aneuploidy 6,12,19,20,32 , which was in line with our results. In contrast, an in vivo study concluded that NO 2 inhalation might reduce the sperm production in rats; 14 Boggia et al found significantly lower sperm total motility, not sperm count, in occupational NO 2 exposed workers; 33 however, the NO 2 exposures in these two studies tended to be much higher than that in the epidemiological studies for general population, which may partly explain the inconsistence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies suggested that exposure to NO 2 (or NO x ) and CO were associated with increased abnormalities in sperm morphology, 12,19 but not associated with sperm concentration, count, motility, nor aneuploidy 6,12,19,20,32 , which was in line with our results. In contrast, an in vivo study concluded that NO 2 inhalation might reduce the sperm production in rats; 14 Boggia et al found significantly lower sperm total motility, not sperm count, in occupational NO 2 exposed workers; 33 however, the NO 2 exposures in these two studies tended to be much higher than that in the epidemiological studies for general population, which may partly explain the inconsistence.…”
Section: Discussionsupporting
confidence: 93%
“…6,11 While a study in China and another study in Poland suggested that SO 2 and NO x might adversely affect sperm morphology, rather than sperm concentration or motility, Farhat et al did not observe any significant association for SO 2 and NO 2 exposures in Brazil. 12,19,20 …”
Section: Introductionmentioning
confidence: 99%
“…Along with an alteration of sperm parameters (other than ejaculate volume and sperm count), they observed a significantly higher level of FSH in the exposed group (mean ± SE: 4.1 ± 0.3 UI/l vs 3.2 ± 0.2; p < 0.05), although this remained within the normal value range [54]. Radwan et al [66] also found a negative association between testosterone levels and exposure to certain air pollutants (PM10, PM2.5, CO and NOx).…”
Section: Impact Of Air Pollution On the Male Gametementioning
confidence: 90%
“…For example, De Rosa et al found an alteration in sperm parameters associated with significantly higher levels of FSH in the group exposed to exhaust, although they remained within the normal value range [54], while Radwan et al reported a negative association between testosterone levels and exposure to certain air pollutants (PM10, PM2.5, CO and NO 2 ) [66].…”
Section: Action As Endocrine Disruptorsmentioning
confidence: 99%
See 1 more Smart Citation